Hexameric-Based Hierarchy in the Sizes of a Cytolysin Pore-Forming Complex - Meijun Liu; Xintao Qin; Menglin Luo; Yi Shen; Jiabin Wang; Jielin Sun; Daniel M. Czajkowsky; Zhifeng Shao (Biomolecules)
Perfringolysin O (PFO) is a prototypical member of a large family of pore-forming toxins (PFTs) that are potent virulence factors for many pathogenic bacteria. One of the most enigmatic properties of these PFTs is how structural changes are coordinated between different subunits within a single complex. Moreover, there are conflicting data in the literature, with gel electrophoresis results apparently showing that pores are only complete rings, whereas microscopy images clearly also show incomplete-ring pores. Here, we developed a novel multi-stack gel electrophoretic assay to finely separate PFO pore complexes and found that this assay indeed resolves both complete- and incomplete-ring pores. However, unexpectedly, we found that the stoichiometries of these complexes are predominantly integral multiples of six subunits. High-resolution atomic force microscopy images of PFO pore complexes also reveal a predominant hexameric-based stoichiometry. We also observed this hexameric-based stoichiometry at the prepore stage and identified a mutant that is kinetically trapped at a hexameric state. Thus, overall, these results reveal a previously unknown hexameric-based structural hierarchy in the PFO complexes. We suggest that the structural coordination within the hexamers is different than between the hexamers and is thus a critical feature of the structural coordination of the complex as a whole.